The effect of niacin and monensin on the performance of young bulls at feedlot - Magliocca, Filelfo de Carvalho; Silveira, Antônio Carlos; Furlan, Luiz Roberto; Arrigoni, Mario de Beni; Costa, Ciniro (Pesquisa Agropecuaria Brasileira, 1994)
The objective of this study was to evaluate the effects of supplementation of combined and single monensin and niacin on the productive performance of crossbred young bulls (european/zebu) aged 11 months and initial average liveweight of 248 kg. The experimental design was a factorial randomized arrangement. The treatments were: T1-check, T2-niacin, T3-monensin and T4-niacin+monensin. All the treatments were isoproteic (11% CP) and isoenergetic (78% TDN), composed of 57.3% roughage and 42.7% concentrate (soybean meal, maize, minerals and buffer). Data was collected over a period of 85 days, with liveweight measured every 28 days. It was conclued that, for this diet, the single supplementation of niacin does not increase the performance of bulls, and therefor it is not recommended. However, the ionophore monensin, single or on in combination with niacin, improves the performance of the animals up to 56 days of feedlot.